2000
DOI: 10.1152/jappl.2000.89.5.1859
|View full text |Cite
|
Sign up to set email alerts
|

A human acinar structure for simulation of realistic alveolar plateau slopes

Abstract: We simulated the intra-acinar contribution to phase III slope (S(acin)) for gases of differing diffusivities (He and SF(6)) by solving equations of diffusive and convective gas transport in multi-branch-point models (MBPM) of the human acinus. We first conducted a sensitivity study of S(acin) to asymmetry and its variability in successive generations. S(acin) increases were greatest when asymmetry and variability of asymmetry were increased at the level of the respiratory bronchioles (generations 17-18) for He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 15 publications
0
75
0
Order By: Relevance
“…It is interesting to explore the underlying theory of N 2 washout and bolus dispersion analysis to understand how gas and aerosol transport mechanisms operating in the same lung structure can be held responsible for the increased S acin and increased bolus dispersion in the deep lung (high VLD). On the basis of N 2 washout theory (11,24) and experiments (29,28), S acin originates from convection-diffusion interaction at the acinar level, where gas convective and gas diffusive transport are of the same order of magnitude, and S acin may be considered independent of gas-mixing events occurring proximal to the acinar lung level. Also, S acin heavily depends on the asymmetry of the acinar lung structure, and a perturbation in the volumetric or cross-sectional asymmetry of parallel intra-acinar units can modify S acin .…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to explore the underlying theory of N 2 washout and bolus dispersion analysis to understand how gas and aerosol transport mechanisms operating in the same lung structure can be held responsible for the increased S acin and increased bolus dispersion in the deep lung (high VLD). On the basis of N 2 washout theory (11,24) and experiments (29,28), S acin originates from convection-diffusion interaction at the acinar level, where gas convective and gas diffusive transport are of the same order of magnitude, and S acin may be considered independent of gas-mixing events occurring proximal to the acinar lung level. Also, S acin heavily depends on the asymmetry of the acinar lung structure, and a perturbation in the volumetric or cross-sectional asymmetry of parallel intra-acinar units can modify S acin .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high airways resistance take longer to clear the nitrogen, and the test can distinguish between obstructions in the large or small airways. Dutrieue et al [43] and Verbanck et al [44] used the MBW test to derive the two variables, Scond (index of conductive ventilation heterogeneity) and Sacin (index of acinar ventilation heterogeneity). In asthmatic subjects, the clinical application of MBW includes evaluation of ventilation heterogeneity after an airway challenge, and analysis of response differences to inhaled steroids when comparing non-extrafine and extrafine particles [45,46].…”
Section: Functional Assessment Of Peripheral Airwaysmentioning
confidence: 99%
“…As mentioned in METHOD, the deformation model did not consider intra-acinar nitrogen concentration inhomogeneity. Simulation studies by Dutrieue et al [11] suggested that diffusion-convection-dependent inhomogeneity in the pulmonary acinus generated phase III slopes. According to their study, it is reasonable that phase III slopes in the present simulation were zero.…”
Section: Validity Of the Lung Deformation Modelmentioning
confidence: 99%
“…8 and 10, respectively. The density change is expressed as ρ(z,t) = ρ 0 (t) (1 -6gtCρ 0 (t)z) -1/2 , if ρ(z,t) < ρ m ρ(z,t) = ρ m , else (11) Accordingly, the displacement function is f(Z, t) = 1.5gtCρ 0 (t) Z 2 , if ρ(z, t) < ρ m f(Z, t) = f(Z m , t) + ρ 0 (Z m -Z)/ρ m , else (12) where (Z m , t m ) are the values of (Z, t) with which the righthand side of Eq. 11 is equal to ρ m .…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation